VIDAS TEST OF IgG AVIDITY FOR DETECTION OF ACUTETOXOPLASMOSIS IN THE EARLY PREGNANCY - Zgaeir, Khawla; Al-Qadi, Ban; Al-Djaily, Khitam (Iraqi Journal of Science, 2024)
Toxoplasmosis is usually asymptomatic, but can have severe consequences if it occurs in immunodeficient subject or fetuses. The diagnosis of toxoplasmosis during pregnancy is often based on maternal serological testing for IgM and IgG anti- Toxoplasma antibodies. Persistence of IgM for long periods, posses’ problems in distinguishing acute from chronic infection. The evaluation of specific IgG avidity enables more accurate dating, since avidity rises progressively during the course of infection.Seventy six women in the first 16 weeks of pregnancy were screened for VIDAS IgM, IgG antibodies and VIDAS toxo-IgG avidity. Low avidity antibodies were demonstrated in 2 (33.3%) of 6 sera positive with IgM assay and 4 (12.12%) of sera positive with IgG assay. Low avidity also detected in 2 (3.27%) of 61 sera negative with IgM. The low avidity suggesting a recent infection, while high avidity in 3 (50%) of the 6 positive IgM and 24 (72.72%) of 33 positive IgG indicating that the infection acquired in the distant past. These findings highlight the value of VIDAS IgG avidity when used in combination with the VIDAS IgM and IgG assay to provide a confirmatory evidence of an acute infection with a single serum specimen for pregnant women.